Profile of Medico-legal Autopsy Cases in a Rural based Tertiary Care Hospital of Central Part of Gujarat during COVID-19 Pandemic: A One Year Retrospective Study - Patel , S H; Gupta , S K; Goswami , D D (Journal of Indian Academy of Forensic Medicine, 2023)
During COVID-19 pandemic, almost all the efforts had been made by each and every state of countries across the world to collect the data on deaths due to COVID-19, however very few articles are available regarding the indirect effects of COVID-19 pandemic. The downfall of unnatural deaths seemed inevitable even during the lockdown period. The study was conducted to analyze the pattern and distribution of autopsy cases related to natural and unnatural deaths during COVID -19 pandemic Financial Year (FY) 2020-21. It was observed that minimum numbers of cases were received during the month of August 2020 and maximum numbers of cases were received in March 2021. A total of approximately 74 % of unnatural deaths registered during the period of COVID-19 FY 2020-2021 were due to injuries. The results of study will contribute to the literature. This study may even help to compare any rise or decline in autopsy cases during COVID-19 pandemic with various states of India as well as foreign countries.